Beneficial Effects of Nutraceuticals, Especially Polyphenols on Canine Health - Domingo Ruiz-Cano; Marino B. Arnao (Pets)
The use of nutraceuticals, mainly phytogenics, is increasingly widespread in animal nutrition, especially in dogs. The materials typically used to provide these very diverse natural compounds come from plants, but lately algae and fungi have also been used. In animal nutrition, these compounds are applied to obtain better results in the production and stability of feed and also as biofunctional substances with benefits for animal health. Polyphenols are natural compounds from the secondary metabolism of plant matter present in animal food (e.g., seeds and nuts, fruits, vegetables, herbs/aromatic plants, spices, cereals, and vegetable oils, among others). Most of the biological effects of these compounds associated with health benefits have been attributed to their antioxidant potential because they can protect cellular elements against oxidative injury, reducing the risk of dysfunctions and diseases associated with oxidative processes. Polyphenols are constituted by multiple families of substances with wide applications in pet therapy and nutrition. In this work, we review the most relevant phytogenic polyphenols, exploring their characteristics, sources, and implications for canine health. Our focus includes the effects on gastrointestinal functions and its microbiota, as well as aspects such as obesity, diabetes, and fat metabolism. Additionally, we examine their impact on cardiovascular, neurological, and immunological systems, along with their potential anti-oncogenic role. Finally, we discuss the overall role of polyphenols in dog diets and their future implications.